Economic reform and institutional change in Central Asia: Towards a new model of the developmental state? - Manuel Stark; Joachim Ahrens (PFH Private Hochschule Göttingen, 2012)
Widely ignoring recommendations from mainstream economics, the some Central Asian countries have achieved remarkable economic growth rates since their transformational recession in the 1990s. While Kazakhstan, Uzbekistan, and Turkmenistan have greatly benefitted from increasing world market prices for natural resources, particularly Kazakhstan and Uzbekistan have pursued distinct country-specific policies and built up politico-institutional structures which may have also contributed to bring about economic and social progress. This paper investigates the politico-institutional foundation of these emerging market economies in Central Asia and addresses the question whether or not these marketdeveloping autocracies are on a way to become developmental states with a firm commitment to economic development in the future.
Keywords: 330; Developmental State; Central Asia; Kazakhstan; Uzbekistan; Wirtschaftsreform; Übergangswirtschaft; Institutioneller Wandel; Entwicklung; Zentralasien